PERSEPSI KOMUNITAS PUNK TENTANG GAYA HIDUP KONSUMTIF GENERASI MILENIAL: (Studi Terhadap Komunitas Punk "Taring Babi") - Ardhi Ridwansyah (2020)
THE PERCEPTION OF PUNK COMMUNITY ON MILLENNIAL GENERATIONS CONSUMPTIVE LIFESTYLE (STUDY ON "TARING BABI" PUNK COMMUNITY) ARDHI RIDWANSYAH Abstract This study discusses the perception of the punk community on the millennial consumptive lifestyle. Punk community was chosen as the subject of research because punk is often perceived poorly in society, but rarely punk is in fact a subculture which certainly has a different lifestyle with the general public giving its perception of a phenomenon. Millennials consumptive lifestyle becomes an object that will be perceived by the punk community. Millennial which is considered as a creative and innovative generation is apparently based on the mass media coverage and research has a tendency to consumptive lifestyle. The purpose of this study is to identify the perception of the punk community regarding the millennial generation's consumptive lifestyles and determine the factors underlying these perceptions. This study used descriptive qualitative method. In this research, the case study used is the "Taring Babi" punk community. The research data were obtained through interviews, observations, and documentation from the "Taring Babi" punk community. The results of this study stated the perception of members of the "Taring Babi" punk community on the millennial generation's consumptive lifestyle is a lifestyle that ensnares millennials in the entrepreneur's business scheme and serves as a market object and consumes goods only to improve social status and follow current trends. Factors underlying these perceptions are values that are shared and past experiences. Keywords: Consumptive, lifestyles, millennial, perception, punk.